The Relationship Between Dual Role Conflict and Family Social Support Towards Fear of Sucsess in Working Mothers - Nanda Widyaningrum; Nugraini Aprilia (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to determine the relationship between dual role conflict and family social support on fear of success in working mothers. Methodology: A total of 84 participants were involved in this study through purposive sampling technique, with data collection using three scales, namely the dual role conflict scale, the family social support scale, and the fear of success scale. Main Findings: These findings indicate that the higher the role conflict experienced by working mothers, the greater their tendency to experience fear of success, while family social support actually acts as a protective factor. Novelty/Originality of this study: The uniqueness of this study lies in the placement of fear of success in the context of social relations of working mothers in the midst of the patriarchal structure of Indonesian society, thus broadening the understanding that fear of success is not merely an individual psychological phenomenon, but is also closely related to social dynamics, gender roles, and domestic pressures faced by women in pursuing success in the public sphere.